2011
DOI: 10.1007/s00296-011-2252-9
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic rheumatic syndromes: report of eight cases and review of literature

Abstract: Malignant neoplasms are associated with a wide variety of paraneoplastic rheumatological syndromes. The paraneoplastic nature should be based on specific criteria. We report a series of eight cases of paraneoplastic rheumatic syndromes revealing an underlying neoplasia. Our series consists of six men and two women, with a mean age of 46.1 (20-69 years). The first case is a hypertrophic osteoarthropathy of Pierre Marie that occurred in a 20-year-old man 1 month after treatment for his nasopharyngeal carcinoma; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 11 publications
0
15
0
10
Order By: Relevance
“…Cancer and autoimmune diseases are often associated with scleroderma, and it is difficult to determine which is the primary disease. Malignant neoplasms may induce a wide variety of paraneoplastic rheumatological syndromes [21,22]. The opposite is also true, as it has been observed that scleroderma caused by the occupational exposure to solvents may frequently result in cancer [8].…”
Section: Case Reportmentioning
confidence: 95%
“…Cancer and autoimmune diseases are often associated with scleroderma, and it is difficult to determine which is the primary disease. Malignant neoplasms may induce a wide variety of paraneoplastic rheumatological syndromes [21,22]. The opposite is also true, as it has been observed that scleroderma caused by the occupational exposure to solvents may frequently result in cancer [8].…”
Section: Case Reportmentioning
confidence: 95%
“…After a review of the literature, only one reported case of a hematological neoplasm was detected after 18 FDG-PET, and it was a young woman with bone inflammatory pain and with severe inflammatory biological syndrome. The case was different from ours where a diagnosis of acute leukemia was given thanks to a 18 FDG-PET exam [2]. …”
mentioning
confidence: 89%
“…Eine systematische Suche nach einem Malignom wird zwar aufgrund der Seltenheit dieser Konstellation nicht empfohlen [21], gerade bei atypischer Präsentation ohne klare Serologie sind aber FragennacheinerSymptomatikund nach regelmäßigen Vorsorgeuntersuchungen oft sinnvoll. Immerhin können verschiedene rheumatische Symptome paraneoplastisch durch ein urologisches Tumorleiden hervorgerufen werden [15,21,26].…”
Section: Worauf Sollten Rheumatologen Achten?unclassified